STANDARDS OF CENTILE SCALES OF MAIN INDICATORS OF PHYSICAL DEVELOPMENT OF PUPILS IN ANDIJAN AT THE AGE OF 12-16 YEARS - M. B.Boykuzieva; G.U.Nazarova; Y.G.Usmanova (American Journals, 2023)
1919 Andijan schoolchildren aged 12-16 were examined. The main indicators of physical development (weight, body length, head and chest circumference) are described in a non-parametric centile (syn. percentile, percentile) method. It is shown that the value of their distribution in the population, their deviation towards increase and decrease is recommended to be used in assessing the physical development of children in the practice of a pediatrician.
Keywords: Schoolchildren, characteristics, physical development, centile scales.